PARADIGMA KRITIS DALAM KURIKULUM, PEMBELAJARAN DAN EVALUASI PENDIDIKAN DI ERA DIGITAL: A SYSTEMATICE LITERATURE REVIEW (SLR) - Harjono; Eka Rosdianwinata; Sholeh Hidayat (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This article explores the application of postmodern theory in education, focusing on curriculum, learning, and assessment in the digital era. Postmodernism emphasizes multiple perspectives, critical reflection, and socially constructed knowledge. Based on a synthesis of 26 accredited journal articles (2018–2025), findings indicate that postmodern education fosters active student engagement, teachers as facilitators, and the integration of digital technology as a reflective learning medium. Practical implications include the development of adaptive curricula, collaborative learning strategies, and authentic assessments evaluating creativity, critical thinking, and social competencies. The study highlights the importance of democratic, contextual, and humanistic education and provides recommendations for teachers, policymakers, and researchers to implement postmodern practices relevant to 21st-century educational challenges. This study employs the Systematic Literature Review (SLR) method, which uses meta synthesis data analysis techniques to collect and analyze various related articles.